Infant with diabetes – a diagnostic challenge for paediatricians - Brandt-Varma, Agnieszka; Myśliwiec, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Common symptoms of diabetes in newborns and infants are uncharacteristic, what often leads to the delay in diagnosis and implementation of proper treatment. Diabetes is rare disease in this life period, but paediatricians should remember about checking glucose level in unwell babies. Children with neonatal diabetes are characterised by low birth weight, significant hyperglycaemia, often with concomitant metabolic acidosis. Hyperglycaemia diagnosed in the neonatal period requires the immediate implementation of insulin therapy, which is essential for proper development and growth of the child. This paper describes a 30-day old boy with permanent neonatal diabetes and all diagnostic and therapeutic difficulties before the final diagnosis was made.